Progression of Notch signaling regulation of B cells under radiation exposure - Shu, Xin; Wang, Jie; Zeng, Huihong; Shao, Lijian (Frontiers in Immunology, 2024)
With the continuous development of nuclear technology, the radiation exposure caused by radiation therapy is a serious health hazard. It is of great significance to further develop effective radiation countermeasures. B cells easily succumb to irradiation exposure along with immunosuppressive response. The approach to ameliorate radiation-induced B cell damage is rarely studied, implying that the underlying mechanisms of B cell damage after exposure are eager to be revealed. Recent studies suggest that Notch signaling plays an important role in B cell-mediated immune response. Notch signaling is a critical regulator for B cells to maintain immune function. Although accumulating studies reported that Notch signaling contributes to the functionality of hematopoietic stem cells and T cells, its role in B cells is scarcely appreciated. Presently, we discussed the regulation of Notch signaling on B cells under radiation exposure to provide a scientific basis to prevent radiation-induced B cell damage.